The method of digital signal processing, adaptive to signal-noise conditions, on the basis of wavelet transformations in reception channels of MIMO radio access systems - Марчук, Артем Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The method of digital signal processing, adaptive to signal- noise conditions, on the basis of wavelet transformations in reception channels of mimo radio access systems is offered in the article. This method are not required calculations of pulse responses of high and low-frequency wavelet filters and optimum parametres of filtering for various SNR values in real time.